2019
DOI: 10.1007/s00701-019-03893-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and prognostic factors in elderly traumatic brain injury patients receiving neurointensive care

Abstract: Background The probability of favorable outcome after traumatic brain injury (TBI) decreases with age. Elderly, ≥ 60 years, are an increasing part of our population. Recent studies have shown an increase of favorable outcome in elderly over time. However, the optimal patient selection and neurointensive care (NIC) treatments may differ in the elderly and the young. The aims of this study were to examine outcome in a larger group of elderly TBI patients receiving NIC and to identify demographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
1
15
1
2
Order By: Relevance
“…Vitamin K antagonists are associated with increased mortality and unfavorable clinical outcome in many TBI studies [4,11,14,28,29,36], but we and others have found no such associations [18,22]. In the current study, anticoagulants were associated with a higher mortality and a decreased rate of favorable clinical outcome in the univariate analysis, but not after adjustment for age, comorbidities, and mechanism of injury.…”
Section: Antithrombotic Agents and Clinical Outcomecontrasting
confidence: 67%
See 1 more Smart Citation
“…Vitamin K antagonists are associated with increased mortality and unfavorable clinical outcome in many TBI studies [4,11,14,28,29,36], but we and others have found no such associations [18,22]. In the current study, anticoagulants were associated with a higher mortality and a decreased rate of favorable clinical outcome in the univariate analysis, but not after adjustment for age, comorbidities, and mechanism of injury.…”
Section: Antithrombotic Agents and Clinical Outcomecontrasting
confidence: 67%
“…The epidemiology of traumatic brain injury (TBI) is changing. As the population ages, the incidence of old TBI victims with pre-injury comorbidities has increased [ 18 , 19 , 31 , 32 ]. This implicates new challenges in TBI care, and one particular concern is the pre-injury use of antithrombotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a pre-injury ASA-PS score of ≥ 3 were substantial (28%) compared to CENTER-TBI which was 11% (Steyerberg et al 2019); the latter is similar to the general trauma population admitted to OUH (10%) (Sovik et al 2014). The more silent comorbidity; antithrombotics, were used by 42% of our TBI patients > 50 years and this compares to other TBI studies, 33-47%, on the elderly population (Gaist et al 2017;Julien et al 2017;Narum et al 2016;Lenell et al 2019). In the total Norwegian population 18% ≥ 40 years use antithrombotic drugs (Berg et al 2017) in line with previously mentioned EU study (Steyerberg et al 2019).…”
Section: Discussionmentioning
confidence: 54%
“…Controversy exists if old patients benefit from aggressive treatment. However, research has demonstrated improved outcome with aggressive treatment in elderly (Herou et al 2015 ; Lenell et al 2019 ; Bus et al 2019 ; Whitmore et al 2012 ). It is worth noting that although pre-injury comorbidity was high in older age groups, about 60% of patients 80–89 years still lived independently at home (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, the GCS score was the second independent factor of good prognosis of AEDH, and a GCS score of 12 was the optimal cutoff value to reflect patient prognosis, as reported in previous studies on ASDH and TBI. [ 2 10 14 15 16 17 18 19 ] Indeed, functional brain damage could be reflected by neurological evaluation, not by radiographical findings, and a GCS score of 12 could be the threshold to indicate whether the brain damage is irreversible.…”
Section: Discussionmentioning
confidence: 99%